Computed tomography in the size measurement of gastric gastrointestinal stromal tumors: Implication to risk stratification and "wait-and-see" tactics. Issue 8 (August 2022) - Li, Yuyi; Chen, Xuyong; Ma, Xu; Lu, Xinliang
Abstract: Introduction: This study aimed to compare the radiologic size of gastric gastrointestinal stromal tumors (GISTs) on computed tomography (CT) with the pathologic size in a Chinese population, and elucidate the potential significance of the CT size in the preoperative risk stratification. Materials and methods: The study enrolled 314 patients treated by endoscopic/surgical resection of gastric lesions that proved postoperatively to be GISTs. Bland-Altman analysis and intraclass correlation coefficient (ICC) were adopted to assess the size agreement between CT and pathology. Independent predictors of risk category underestimation and the optimal cut-off value of CT size were determined by logistic regression analysis and the receiver operating characteristic (ROC) curve. Results: CT underestimated gastric GISTs size by 0.30 cm [95% confidence interval (CI): (−0.42, - 0.19); p < 0.001]. In the subgroup analysis, the size underestimation was 0.10 cm in GISTs ≤ 5 cm [95% CI: (−0.19,  −0.01); p = 0.024]; and 0.75 cm in GISTs >5 cm [95% CI: (−1.05, 0.45), p < 0.001]. Though ICC values showed well reliability for the corresponding pathologic size, with 0.95 in all size, 0.86 in size ≤ 5 cm, and 0.92 in size >5 cm respectively. Risk underestimation by CT imaging mainly occurred in gastric GISTs with smaller size (≤5 cm; p = 0.010) and lower mitotic index (≤5 per 50 high-power fields; p = 0.011). CT size of 3.65 cm was defined as an absolute cut-off to differentiate intermediate/high-risk patients from low-risk group, with 87.5% sensitivity at a specificity of 57.8%. Conclusion: Preoperative CT underestimated the mean size by 0.30 cm in gastric GISTs. A CT size of 3.65 cm would facilitate the selection of potential intermediate/high-risk patients, instant intervention should be encouraged in the absence of contraindications.